The inn at Angel Island - Kinkade, Thomas, 1958-2012 (Kinkade, Thomas, 1958-2012. Angel Island novel., 2010)
Liza Martin arrives on Angel Island to sell the inn she and her brother inherited from their aunt, so she can bolt back to her busy life in Boston. But back home awaits a broken marriage and an unstable career is much for her to resolve before her departure--and it is going to take a band of angels to mend her broken wings and redirect her soul.